2006
DOI: 10.1007/s11172-006-0434-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tri-and tetraalkynylgermanes

Abstract: A straightforward synthesis of tetra and trialkynylgermanes by reactions of compounds containing Ge-N or Ge-Cl bonds with alk 1 ynes was proposed. Reactions of appropriate amino or halogermanes with alk 1 ynes were effective only in the presence of an equivalent amount of zinc dihalide.Acetylene derivatives of germanium, in which the Ge atom is bound to sp hybridized C atoms, are well known and are conventionally synthesized by reactions of alkali metal or magnesium alkynides with halogermanes. 1,2However, dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…No reaction was observed when the tris­(alkynide) 1 was stirred with PhCCH at room temperature or heated for more than 30 h at 80 °C. It has been reported that the related reaction of (R 2 N) n GeR′ 4– n with alkyl- or arylacetylenes R″CCH to yield R′ 4– n Ge­(CCR″) n ( n = 0, 1) required stoichiometric amounts of Lewis acidic zinc dihalides for activation . The unique reaction and the unexpectedly high reactivity of 4b is a clear indication of the cooperative activation of the Ge–N bond by the Lewis acidic Ga t Bu 2 group.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…No reaction was observed when the tris­(alkynide) 1 was stirred with PhCCH at room temperature or heated for more than 30 h at 80 °C. It has been reported that the related reaction of (R 2 N) n GeR′ 4– n with alkyl- or arylacetylenes R″CCH to yield R′ 4– n Ge­(CCR″) n ( n = 0, 1) required stoichiometric amounts of Lewis acidic zinc dihalides for activation . The unique reaction and the unexpectedly high reactivity of 4b is a clear indication of the cooperative activation of the Ge–N bond by the Lewis acidic Ga t Bu 2 group.…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that the related reaction of (R 2 N) n GeR′ 4−n with alkyl-or arylacetylenes R″CCH to yield R′ 4−n Ge(CCR″) n (n = 0, 1) required stoichiometric amounts of Lewis acidic zinc dihalides for activation. 18 The unique reaction and the unexpectedly high reactivity of 4b is a clear indication of the cooperative activation of the Ge−N bond by the Lewis acidic Ga t Bu 2 group. Despite the prolonged heating of the reactants at 60 °C during the synthesis of compound 5, no indication for a cis/trans isomerization of the vinyl groups was found.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Alkynylgermanium compounds can be prepared by various methodologies involving classical stoichiometric organometallic routes that can be classified into three groups, i.e., the reactions of organogermanium halides with metal acetylides, germylation of terminal alkynes, and modification of preformed alkynylgermanes 8 (for a recent review see ref ).…”
Section: Introductionmentioning
confidence: 99%
“…Later, Andreev expanded upon this concept by devising a zinc halide-assisted sp CÀ H germylation involving the reaction between alkynes and aminogermanes. [171] Very recently, Bannykh and Pihko disclosed a metal-free sp CÀ H silylation protocol. Here, a quaternary ammonium pivalate serves as the catalyst, whilst N,O-bis(silyl)acetamides as silylating agents (Figure 44).…”
Section: From Aminosilanesmentioning
confidence: 99%
“…Finally, the authors proposed two independent mechanistic pathways. Later, Andreev expanded upon this concept by devising a zinc halide‐assisted sp C−H germylation involving the reaction between alkynes and aminogermanes [171] …”
Section: Synthesis Of 1‐silyl‐1‐alkynesmentioning
confidence: 99%